Optimizing Outcomes in Immunocompromised Hosts: Understanding the Role of Immunotherapy in Invasive Fungal Diseases - Ravikumar, Sharada; Win, Mar Soe; Chai, Louis Yi Ann (Frontiers in Microbiology, 2015)
A major global concern is the emergence and spread of systemic life –threatening fungal infections in critically ill patients. The increase in invasive fungal infections, caused most commonly by Candida and Aspergillus species, occurs in patients with impaired defenses due to a number of reasons such as underlying disease, the use of chemotherapeutic and immunosuppressive agents, broad-spectrum antibiotics, prosthetic devices and grafts, burns, neutropenia and HIV infection. The high morbidity and mortality associated with these infections is compounded by the limited therapeutic options and the emergence of drug resistant fungi. Hence, creative approaches to bridge the significant gap in antifungal drug development needs to be explored. Here, we review the potential anti-fungal targets for patient-centered therapies and immune-enhancing strategies for the prevention and treatment of invasive fungal diseases.